PENGARUH KUALITAS PRODUK, WORD OF MOUTH, DAN BRAND IMAGE TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA PRODUK AIR MINERAL DALAM KEMASAN MEREK VUROTA DI SITUBONDO - Aziza, Wahyu Nur; Ediyanto, Ediyanto; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2025)
In an increasingly competitive business world, companies are required to not only offer quality products but also be able to create a positive customer experience. Consumer satisfaction is one of the main factors that determine the sustainability of a business, especially in an industry that has many competitors, such as bottled mineral water. The purpose of this study is to analyze and test the influence of Product Quality, Word of Mouth, and Brand Image. This research is an explanatory study. The population in this study was residents of Griya Panji Mulya Situbondo. The sampling technique was determined by probability sampling. The data analysis and hypothesis testing in this study used IBM SPSS Statistics 22 - Structural Equation Model - Partical Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.2 application, show that Product Quality has a significant positive effect on Purchasing Decisions, the Word of Mouth has a significant negative effect on Purchasing Decisions, the Brand Image has a significant positive effect on Purchasing Decisions, the Product Quality has a negative but not significant positive effect on Consumer Satisfaction, the Word of Mouth has a significant positive effect on Consumer Satisfaction, the Brand Image has a positive but not significant effect on Consumer Satisfaction, the Purchasing Decision has a significant positive effect on Consumer Satisfaction. The results of the indirect influence hypothesis test show that Product Quality has a positive but insignificant effect on Consumer Satisfaction through Purchasing Decisions, the Word of Mouth has a negative but insignificant effect on Consumer Satisfaction through Purchasing Decisions, Brand image has a negative but insignificant effect on Consumer Satisfaction through Purchasing Decisions.